Effect of the carrier gas on the structure and composition of Co–Ni bimetallic nanoparticles generated by spark ablation. (May 2023) - Ternero, Pau; Sedrpooshan, Mehran; Wahlqvist, David; Meuller, Bengt O.; Ek, Martin; Hübner, Julia-Maria; Westerström, Rasmus; Messing, Maria E.
Abstract: Spark ablation is a versatile technique for producing pure size-selected nanoparticles. The carrier gas used in spark ablation affects the nanoparticles' generation, crystalline structure, and chemical composition. The comprehension of this phenomenon can contribute to the design of nanoparticles with tailored properties. In this paper, we evaluate the effects of reducing (95%N 2 + 5%H 2 ), inert (N 2 ), and oxidative (air) carrier gases in a spark ablation setup with Co–Ni alloyed electrodes. The agglomerates' particle size distribution, morphology, structure, and composition were highly dependent on the carrier gas, especially its relative oxygen content. The agglomerates were then sintered into compacted particles. Three different crystalline structures and chemical compositions were observed with X-ray diffraction and confirmed with transmission electron microscopy for the compacted particles. For 95%N 2 + 5%H 2 and air, single-phase (Co, Ni) and (Co, Ni)O particles were identified, respectively, whereas for N 2, two-phase (Co, Ni) and (Co, Ni)O particles were obtained. This work opens up new possibilities of tuning the structure and composition, i.e., distribution of metallic and oxide phases, of the produced particles and thus tailor their properties for specific applications by simply changing the carrier gas. Highlights: Effect of chemically different carrier gases on the nanoparticle structure. Different nanoparticle compositions obtained depending on the carrier gas used. The nanoparticle structure and composition determine the magnetic ordering. Simple and versatile approach to design nanoparticles with tailored properties.